Anterior surgery for adolescent idiopathic scoliosis - Helenius, Ilkka (Springer Berlin Heidelberg, 2012)
Anterior open scoliosis surgery using the dual rod system is a safe and rather effective procedure for the correction of scoliosis (50–60 %). Thoracic hypokyphosis and rib hump correction with open anterior rather than posterior instrumentation appear to be the better approaches, although the latter is somewhat controversial with current posterior vertebral column derotation devices. In patients with Risser grade 0, hyperkyphosis and adding-on may occur with anterior thoracic spine instrumentation. Anterior thoracoscopic instrumentation provides a similar correction (65 %) with good cosmetic outcomes, but it is associated with a rather high risk of instrumentation (pull-out, pseudoarthrosis) and pulmonary complications. Approximately 80 % of patients with adolescent idiopathic scoliosis (AIS) curves of >70° have restrictive lung disease or smaller than normal lung volumes. AIS patients undergoing anterior thoracotomy or anteroposterior surgery will demonstrate a significant decrease in percentage of predicted lung volumes during follow-up. The thoracoabdominal approach and thoracoscopic approach without thoracoplasty do not produce similar changes in detrimental lung volume. In patients with severe AIS (>90°), posterior-only surgery with TPS provides similar radiographic correction of the deformity (44 %) with better pulmonary function outcomes than anteroposterior surgery. Vascular spinal cord malfunction after segmental vessel ligation during anterior scoliosis surgery has been reported. Based on the current literature, the main indication for open anterior scoliosis instrumentation is Lenke 5C thoracolumbar or lumbar AIS curve with anterior instrumentation typically between T11 and L3.